2018
DOI: 10.5435/jaaosglobal-d-18-00068
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-day Complications and Readmission Rates in Elderly Patients After Shoulder Arthroplasty

Abstract: Introduction:Shoulder arthroplasty procedures are increasingly being performed in older patients despite an increased perioperative risk. The purpose of this study is to determine the complications and 30-day readmission rates in the elderly population after shoulder arthroplasty and hemiarthroplasty.Methods:Total shoulder arthroplasty, reverse total shoulder arthroplasty, and hemiarthroplasty cases were collected from the National Surgical Quality Improvement Program database from 2006 to 2015. The 30-day com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 29 publications
2
22
1
2
Order By: Relevance
“…These complication rates resulted in very low reoperation rates between 0 and 2%. [17][18][19] Clark et al 5 described an overall mortality of 19% in the median time to death of 67.7 months in the study population. The data are promising and lend support to RTSA for elderly patients.…”
mentioning
confidence: 87%
“…These complication rates resulted in very low reoperation rates between 0 and 2%. [17][18][19] Clark et al 5 described an overall mortality of 19% in the median time to death of 67.7 months in the study population. The data are promising and lend support to RTSA for elderly patients.…”
mentioning
confidence: 87%
“…With approximately 70,000 surgeries each year, TSA has become the fastest growing total joint replacement procedure in the United States [ 1 , 2 ]. The number of procedures is expected to further increase given the aging population and the notable success of TSA procedures in restoring function and reducing pain [ 3 , 4 ]. TSA procedures are used to treat various degenerative conditions of the shoulder common in older adult populations [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The number of procedures is expected to further increase given the aging population and the notable success of TSA procedures in restoring function and reducing pain [ 3 , 4 ]. TSA procedures are used to treat various degenerative conditions of the shoulder common in older adult populations [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shin et al performed a large database study on 27,072 shoulder arthroscopies and found a surgical complication rate of 7.9% and block-related complication rate of 0.59% [21]. Koh et al evaluated 11,450 shoulder arthroplasty patients finding a complication rate of 7.6% [22]. While the rate of complications seen in our study is similar to the large database meta-analyses [20][21][22], all are still lower than described by Vandepitte et al who compared liposomal bupivacaine added to bupivacaine vs. bupivacaine interscalene blocks [16].…”
Section: Discussionmentioning
confidence: 99%
“…Koh et al evaluated 11,450 shoulder arthroplasty patients finding a complication rate of 7.6% [22]. While the rate of complications seen in our study is similar to the large database meta-analyses [20][21][22], all are still lower than described by Vandepitte et al who compared liposomal bupivacaine added to bupivacaine vs. bupivacaine interscalene blocks [16]. ey found that 17 out of 26 patients in the liposomal bupivacaine group reported adverse events compared to 10 out of 24 in the bupivacaine group.…”
Section: Discussionmentioning
confidence: 99%